A Thermostat‐Consistent Fully Coupled Molecular Dynamics—Generalized Fluctuating Hydrodynamics Model. Issue 4 (25th November 2020) - Liu, Xinjian; Korotkin, Ivan; Rao, Zhonghao; Karabasov, Sergey
Abstract: The previously developed multiscale method for concurrently coupling atomistic and continuum hydrodynamic representations of the same chemical substance is extended to consistently incorporate the Langevin‐type thermostat equations in the model. This allows not only to preserve the mass and momentum conservation laws based on the two‐phase flow analogy modeling framework but also to capture the correct local fluctuations and temperature in the pure atomistic region of the hybrid model. Numerical results for the test problem of equilibrium isothermal fluctuations of SPC/E water are presented. Advantages of using local thermostat equations adjusted for the multiresolution model for accurately capturing of the local water density in the atomistic part of the hybrid simulation domain are discussed. Comparisons with the reference pure all‐atom molecular dynamics simulations in GROMACS show that the suggested hybrid models are by a factor of 5–20 faster depending on the simulation domain size. Abstract : A multiscale formulation is developed to concurrently couple atomistic and continuum hydrodynamic representations of the same chemical substance with a molecular dynamics (MD) thermostat in both parts of the model. Numerical results for the test problem of equilibrium isothermal fluctuations of SPC/E water are presented showing a 5–20‐fold solution acceleration in comparison with all‐atom MD in GROMACS.